STRATEGI PEMBANGUNAN DESA WISATA KANDRI MENUJU KESEJAHTERAAN MASYARAKAT - Neny Marlina (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2015)
The research is entitled “Village Development Strategy towards Communal Prosperity: Case Study of Kandri Tourism Village Gunungpati.” The research is located in Kandri Tourism Village Gunungpati Semarang with the purpose of providing description upon the involvement of local actors (government, private, society) in exercising the strategy of tourism village development. Through the strategy, the depiction of the impact of development strategy on the communal prosperity is acquired. The employed method is qualitative research method with case study approach and informant selection technique is using purposing sampling technique. The data is primary and secondary data. The primary data is acquired from the interviewing with the informant result with observation, while the secondary is acquired by supporting related literature.After the issue of Semarang Mayor Decree Number 556/407 about the status of Kandri Kelurahan as Tourism Village, which in consequences the tourism activity is being more developed. Kandri Tourism Village is devided into four tourism sectors, which are natural, culinary, education and cultural tourism. The tourism village development is implemented by partnership strategy, promotion and exhibiting festival. The partnership of the management of Kandri village with the other parties such as government, scholars and privates are implemented as the form of supporting force towards the development of the three year old tourism village. The social movement through tourism awareness social groups gives more spaces on the society to develop according to the potential. The tourism village development village opens business and working opportunity aside from farming, plantation and animal husbandry.Base on the research, the conclusion may be drawn as the existence of tourism village is indeed encouraging social changes toward prosperity that may be seen from the level of participation and economy of the society. The partnership, promotion and festival activities are methods to encourage the participation of the society in conserving the natural resources and at the same time increasing the quality of human resource in Kandri Tourism Village.